Extraction of essential oil from Cinnamomum Zeylanicum by various methods as a perfume oil - Saleeza Azura, Sulaiman (2013)
Cinnamomum Zeylanicum is a very popular spice and very useful substances in medicines and food,said to be originated from the island Sri Lanka,southeast of India.The plant is also playing an important role in aromatherapy due to its chemical constituent and also its aroma and scent.It contains cinnamaldehyde,an aromatic compound that have a very pleasant smell that can relax and soothe the mind and body, and also eugenol that have a strong aromatic odor and a spicy,pungent taste.The aims of this research are to extract and obtain essential oils from Cinnamomum zeylanicum using hydro distillation technique and ultrasonic extraction method, to analyze the chemical compound present in the essential oil using Gas Chromatography-Mass Spectrometer (GCMS),and to use the extracted essential oil in aromatherapy as a perfume oil.The hydro distillation method is used to obtain the essential oil from Cinnamomum Zeylanicum by grinding the leaves into a fine powder, weighing and then extracted the essential oil by Soxhlet apparatus while by ultrasonic extraction, the samples will soak in a mixture of ethanol and water in ultrasonic bath then will centrifuge to separate the solid and liquid.Next, the sample will be analyzed by GS/MS technique after rotary evaporating to separate between oil and water,in order to determine the chemical composition in the leaves of the plant.The percentage of essential oil yield is calculated as the weight of essential oils divided by the weight of leaf powder.Then,the essential oil will be tested as aromatherapy oil by using sensory evaluation.The result showed only essential oil by hydrodistillation contains eugenol and others 29 volatile and aromatic compounds while the essential oil by ultrasonic extraction,it contains no eugenol but more antioxidant compound.The time of extraction and weight of dry leaves should be varied in order to get better results in term of yield and active compound in the essential oil.